2004
DOI: 10.1094/cchem.2004.81.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Using an In‐Line Slit‐Die Viscometer to Study the Effects of Extrusion Parameters on Corn Melt Rheology

Abstract: An in‐line slit‐die viscometer (SDV) was used to measure the viscosity of a melt extrudate independently of the extruder operating conditions. The melt produced by extrusion of the corn grits followed a power law rheological model. The viscosity of the melt and extrusion parameters such as specific mechanical energy (SME), torque, and die pressure decreased with increasing moisture content. The degree of starch gelatinization increased when barrel temperature increased from 90 to 130°C. At temperatures higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 34 publications
4
40
0
4
Order By: Relevance
“…The utilization of the Power Law model to describe the flow behavior of cereal grains has been confirmed by several authors (LI;CAMPANELLA;HARDACRE, 2004;CARVALHO;ASCHERI;MITCHELL, 2004;ALAVI;CHEN;RIZVI, 2002;SINGH;SMITH, 1999;BAGLEY;DINTZIS;CHAKRABARTI, 1998;PADMANABHAN;BHATTACHARYA, 1991;SENOUCI;SMITH, 1988).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The utilization of the Power Law model to describe the flow behavior of cereal grains has been confirmed by several authors (LI;CAMPANELLA;HARDACRE, 2004;CARVALHO;ASCHERI;MITCHELL, 2004;ALAVI;CHEN;RIZVI, 2002;SINGH;SMITH, 1999;BAGLEY;DINTZIS;CHAKRABARTI, 1998;PADMANABHAN;BHATTACHARYA, 1991;SENOUCI;SMITH, 1988).…”
Section: Resultsmentioning
confidence: 82%
“…It is known that extruded foods behave as non-Newtonian fluids, and their viscosity can be described by the Power Law model (CARVALHO; ASCHERI; MITCHELL, 2004;LI;CAMPANELLA;HARDACRE, 2004;SINGH;SMITH, 1999;EERIKAINEN;LINKO, 1998;RAO;ANANTHESWARAN 1982;REMSEN;CLARK, 1978). However, little is known about the rheological behavior of ingredients submitted to the characteristic processes in the feed industry.…”
Section: Introductionmentioning
confidence: 99%
“…The in-line viscosity at die of each treatment was calculated according to the method described by Li et al (2004) using the formula below, where g is the apparent viscosity (Pa s), s the shear stress (Pa), c the shear rate (s À1 ), DP the die pressure drop (Pa), H, L and B the known geometries of viscometer channel (mm), and s the velocity of extrudate coming out from the die (mm/s)…”
Section: Sample Collection and Determination Of System Parametersmentioning
confidence: 99%
“…Different techniques have long been used to carry out these measurements. They vary from off-line determinations mainly through capillary rheometers (Parker, Lai-Fook, Ollet & Smith, 1989;Madeka & Kokini, 1992;Sandoval & Barreiro, 2007), to the most popular in use, on-line measurements at the extruder die (e.g., Harper, Rhodes & Wanninger, 1971;Bhattacharya & Padmanhabhan, 1992;Vergnes, Della Valle, & Tayeb, 1993;Drozdek & Faller, 2002;Li, Campanella, & Hardacre, 2004 for instance). Using the latter, Cho and Rizvi (2009) recently showed that whey protein addition slightly decreased viscosity of starch based melts for extrusion, and that it could affect cellular structure.…”
Section: Introductionmentioning
confidence: 99%